HUKUM YANG MEMPERLAKUKAN ORANG “TIDAK SAMA” DI HADAPAN HUKUM (ITS REALITY: EVERYONE NOT EQUALITY BEFORE THE - Fitria, Yenni; Wibowo, Adhi (Ensiklopedia of Journal, 2024)
Equality before the law is one of the most fundamental normative principles or principles. This means that the law does not discriminate against anyone who comes to ask for justice. That is the ideal of law, that is the law that should be enforced anytime and anywhere. Meanwhile, in reality, we see that there is another principle that is looming, as we often hear in the expression "the law is sharp downwards but blunt upwards." The law that people actually experience and appreciate is that there are differences before the law, that is the sociology of law. What can I do, this is the behavior of law, that law can change due to the influence of stratification in society, morphology, culture, organization and social control.Keywords: Law, People, Before the Law